2015
DOI: 10.1073/pnas.1421632111
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum dot/antibody conjugates for in vivo cytometric imaging in mice

Abstract: Multiplexed, phenotypic, intravital cytometric imaging requires novel fluorophore conjugates that have an appropriate size for long circulation and diffusion and show virtually no nonspecific binding to cells/serum while binding to cells of interest with high specificity. In addition, these conjugates must be stable and maintain a high quantum yield in the in vivo environments. Here, we show that this can be achieved using compact (∼15 nm in hydrodynamic diameter) and biocompatible quantum dot (QD) -Ab conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 27 publications
0
77
0
Order By: Relevance
“…By employing this method, the disadvantages associated with fluorescently labeled antibodies such as low photo-stability, small multiphoton action cross-section and asymmetric emission are no longer an issue. 17 In order to achieve superior biomedical properties, Osifeko and Nyokong have proposed hybrid nanoparticles with phthalocyanines in combination with QDs, magnetic nanoparticles and gold nanoparticles (GNPs). Their results showed an increase in triplet quantum yields for phthalocyanines in the presence of QDs and GNPs, while a general decrease in fluorescence quantum yields for them was observed in the presence of all the nanoparticles investigated (QDs, GNPs and magnetic nanoparticles).…”
Section: Imagingmentioning
confidence: 99%
“…By employing this method, the disadvantages associated with fluorescently labeled antibodies such as low photo-stability, small multiphoton action cross-section and asymmetric emission are no longer an issue. 17 In order to achieve superior biomedical properties, Osifeko and Nyokong have proposed hybrid nanoparticles with phthalocyanines in combination with QDs, magnetic nanoparticles and gold nanoparticles (GNPs). Their results showed an increase in triplet quantum yields for phthalocyanines in the presence of QDs and GNPs, while a general decrease in fluorescence quantum yields for them was observed in the presence of all the nanoparticles investigated (QDs, GNPs and magnetic nanoparticles).…”
Section: Imagingmentioning
confidence: 99%
“…These multiplexed probes were applied for intravital cytometric in vivo imaging and single-cell labelling in bone marrow. Using a calvarial bone window system, the authors showed that the QD conjugates efficiently diffused into the bone marrow and labelled single cells of rare populations of hematopoietic stem and progenitor cells [85]. Shi et al have designed the multifunctional graphene oxide QDsdecorated magnetic nanoplatform enabling the challenging task of capturing rare Glypican-3-expressing Hep G2 circulating liver cancer tumour cells in tumour cell-enriched blood preparations containing as few as 10 cancer cells in 15 mL [86].…”
Section: In Vivo Imaging Using Quantum Dotsmentioning
confidence: 99%
“…4 illustrates two in vivo live-animal imaging applications of highly fluorescent semiconductor QDs (Fig. 4A) (89) and near-IR fluorescing SWNTs (Fig. 4B) (90).…”
Section: Inorganic Nanoparticles and Related Nanomaterials In Biomedimentioning
confidence: 99%